Hydrazonoyl Chlorides as Precursors for Synthesis of Novel Bis-Pyrrole Derivatives - Kheder, Nabila Abdelshafy (Molecules, 2016)
A convenient synthesis of some novel bis-pyrrole derivatives via hydrazonoyl halides is described. Antimicrobial evaluation of some selected examples of the synthesized products was carried out. The bis-pyrrole derivative having chloro substituents showed good activity against all of the used microbes. The molecular docking of the bis-pyrrole derivatives was performed by the Molecular Operating Environment (MOE) program.